THE EFFECT OF FINANCIAL LITERACY ON THE FINANCIAL MANAGEMENT OF MSMEs IN THE FOOD AND BEVERAGE SECTOR IN SUBANG DISTRICT - Titin Kartini; Rakhamayudhi Rakhamayudhi (Sean Institute, 2022)
The purpose of this study is to determine the effect of financial literacy on the financial management of MSMEs in the food and beverage sector in Subang district. The method used in this research is descriptive and verification, the sampling method is purposive sampling. with a total sample of 77 SMEs. The data analysis method used is simple regression analysis. The results of the study stated that there was a positive effect of financial literacy on the financial management of MSMEs in the food and beverage sector in Subang Regency. The magnitude of the effect of financial literacy on financial management is 72%.